Islam and the political theory, governance and international relations - Sabet, Amr G. E. (Decolonial studies, postcolonial horizons., 2008)
This book compares Islamic and Western political formulations, highlighting areas of agreement and disparity. Building on this analysis, the author goes on to show that political Islam offers a serious alternative to the dominant political system and ideology of the West.Sabet argues that rather than leading to a "Clash of Civlizations" or the assimilation of Islam into the Western system, a positive process of interactive self-reflection between Islam and liberal democracy is the best way forward.Beginning this process, Sabet highlights key concepts of Islamic political thought and brings them into dialogue with Western modernity. The resulting synthesis is essential reading for advanced undergraduate and graduate students of Islamic and Middle Eastern politics, political theory, comparative politics and international relations.